1995
DOI: 10.1021/ac00120a026
|View full text |Cite
|
Sign up to set email alerts
|

Use of Non-Cross-Linked Polyacrylamide for Four-Color DNA Sequencing by Capillary Electrophoresis Separation of Fragments up to 640 Bases in Length in Two Hours

Abstract: Four-color DNA cycle sequencing was performed on an M13mp18 template using dye-labeled primers. Sequencing fragments were separated by capillary electrophoresis at 60 degrees C and at an electric field of 150 V/cm. The sieving medium was 5%T, non-cross-linked polyacrylamide in 7 M urea. The use of high temperature for the separation reduces formation of secondary structures in the sequencing fragments, generating a sequence that is free of compressions without the use of strongly denaturing gels. The use of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 0 publications
3
87
0
Order By: Relevance
“…The large surface to volume ratio of the capillary permits higher electric fields that result in efficient and rapid separation of products. [29] Some groups have used non-crosslinked polymer-filled capillaries for restriction fragment analysis [30] and DNA sequencing [31][32][33]. This technology allows replacement of separation matrix after each run permitting more runs per capillary, automation, and easier usage.…”
Section: Post-pcr Detectionmentioning
confidence: 99%
“…The large surface to volume ratio of the capillary permits higher electric fields that result in efficient and rapid separation of products. [29] Some groups have used non-crosslinked polymer-filled capillaries for restriction fragment analysis [30] and DNA sequencing [31][32][33]. This technology allows replacement of separation matrix after each run permitting more runs per capillary, automation, and easier usage.…”
Section: Post-pcr Detectionmentioning
confidence: 99%
“…28,29 In 1995, Dovichi et al reported the first separation of DNA sequencing fragments at 60˚C with non-cross-linked polymer capillary electrophoresis. 30 This temperature was sufficiently high to eliminate any sequencing artifacts, thereby generating a high-quality sequence. Analytical chemists seized the opportunity, addressing the problem of achieving a high throughput with good sensitivity, says H. Kambara at Hitachi's Central Research Laboratory, Japan.…”
Section: ·3 Capillary Electrophoresis For Dna Sequencingmentioning
confidence: 99%
“…Zhang et al 1995Zhang et al , 1999Bashkin et al 1996a,b;Carrilho et al 1996;Kheterpal et al 1996;Dovichi 1997Dovichi , 1999Kheterpal and Mathies 1999;Pang et al 1999;Crabtree et al 2000;Gao and Yeung 2000;McWhorter and Soper 2000) to provide high throughput analysis of DNA fragments.…”
Section: Capillary-based Sequencersmentioning
confidence: 99%
“…At the detection end of the capillaries, the samples flow through a sheath flow cuvette detector (originally developed by Dr. Norman Dovichi, University of Alberta, Edmonton, Canada; http://www. chem.ualberta.ca/faculty/dovichi.htm; Swerdlow et al 1991;Zhang et al 1995;Service 1998c) to eliminate capillary wall scattering and to provide continuous excitation and detection. Uncoated capillaries are used and are dynamically coated with a polymer such as POP-6 to control electro-osmotic flow.…”
Section: Capillary-based Sequencersmentioning
confidence: 99%